Ropemasks (and gloves) 2010-2022 /. - Pot, Bertjan; Van Leemput, Lien ([Sint-Amandsberg] : Art Paper Editions, 2022)
A collection of Bertjan Pots Ropemasks and Gloves, made from 2010 to 2022.00Bertjan Pot's most well known product is probably the Random Light (1999) but the Masks he makes out of colourful rope have also drawn quite some attention. Both the Random light and Masks started as a material research, which is basically the starting point of each work created by Bertjan Pot. The outcome is usually an interior product showing a fascination for techniques, structures, patterns and colours. Most experiments start quite impulsively by a certain curiosity for how things would function or how something would look. From there, Bertjan Pot takes on challenges with or without manufacturers to explore possibilities and push boundaries. The reward for each challenge is a new one.
kunstcatalogus
Keywords: Pot, Bertjan; Masks